The influence of the probiotic “Bioseven” on indicators of survival and growth of calves in the early postnatal period - A. V. Dyuba; V. P. Lyasota (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Dairy cattle breeding is one of the promising areas of agriculture. With a systematic approach and modern technologies, it is a highly profitable agrarian business that is dynamically developing. According to experts, the competitiveness and profitability of the industry can be increased due to the use of natural feed additives and preparations to obtain ecologically safe products for humans. Among them, preparations of microbiological origin are increasingly used, in particular, probiotics, which contain living microorganisms useful for the macroorganism. These drugs are used for prophylactic or therapeutic purposes. It is known that most microorganisms inhabiting the intestines are safe and do not cause diseases, but there is a constant competition between bacteria of different species for space and nutrients. The inconsistency of the microclimate parameters in the calf pens had a direct negative effect on the calf's body, especially in the early postnatal period. In particular, the deviation from the temperature balance, increased air humidity, and the presence of drafts caused a violation of the heat exchange processes of the calves' body with hypothermia and overheating of the body, and, as a result, provoked the frequent occurrence of respiratory diseases. In addition, increased air humidity and high microbial pollution caused the emergence of diseases with functional disorders in the digestive tract due to an imbalance of normal flora and increased activity of the development of transit microbes from the external environment, which negatively affected the homeostasis of the calves' body, weakened the natural resistance of calves, their growth, preservation and often led to the death of animals. Oral use of the probiotic “Bioseven” in a dose of 5.0 g (1.5·109 CFU/cm3) based on 10 kg of live weight ensured the complete preservation of the herd of young calves, accelerated their growth energy, as evidenced by exterior indicators of the animals of the experimental group against the control and probable (P < 0.05) average daily gains in live weight – 1.236 ± 0.37 kg/day versus 1.002 ± 0.41 kg/day in the control group of calves. In further studies, we used a dose of the probiotic “Bioseven” – 5.0 g (1.5·109 CFU/cm3) based on 10 kg of live weight, as the optimal dose of the experimental drug, established by the results of research. Comparative results of studies of growth indicators in the calves of the experimental group showed a significant advantage in the actual probable (Р < 0.01) increase in their live weight during the experimental period, which exceeded the similar indicators of the control by 23.6 %. The results of studies of indicators of average daily live weight gain were significantly (Р < 0.05) higher than those of control calves by 28.5 % (Р < 0.01), which testified to the effectiveness of the use of the probiotic “Bioseven” in young calves. Taking into account the obtained results, it becomes clear that the components of the probiotic drug “Bioseven” have a positive effect on the formation of cicatricial digestion in calves.